Vocational psychology Agency, equity, and well-being. [article]. - Brown, Steven D.
The present review organizes the vocational psychology literature published between 2007 and 2014 intro three overarching themes : Promoting (a) agency in career development, (b) equity in the work force, and (c) well-being in work and educational settings. Research on career adaptability, self-efficacy beliefs, and work volition is reviewed in the agency section, with the goal of delineating variables that promote or constrain the exercise of personal agency in academic and occupational pursuits. The equity theme covers research on social class and race/ethnicity in career development; entry and retention of women and people of color in science, technology, engineering, and math (STEM) fields; and the career service needs of survivors of domestic violence and of criminal offenders. The goal was to explore how greater equity in the work force could be promoted for these groups. In the well-being section, we review research on hedonic (work, educational, and life satisfaction) and eudaimonic (career calling, meaning, engagement, and commitment) variable, with the goal of understanding how well-being might be promoted at school and at work. Future research needs related to each theme are also discussed. -- (from the authors)